1974
DOI: 10.1044/jshd.3903.366
|View full text |Cite
|
Sign up to set email alerts
|

Variations in Velopharyngeal Closure Assessed by Endoscopy

Abstract: Velopharyngeal closure may be observed directly with a laryngeal telescope 6 mm in diameter. The speech sample used during the endoscopic examination should include several repetitions of a plosive consonant to insure sustained closure. Thirty-four normal subjects were observed, and the percentage of occurrence in four categories of velar and lateral wall approximation was calculated and categorized. To confirm the observations, cineradiographic (lateral and submentovertical projections) and telescopic observa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1982
1982
2007
2007

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Over a several year period the author first categorized lateral wall movement among normal patients (Zwitman, 1974); then in patients with velar insufficiency (Zwitman, 1976). In the second study the findings revealed that during phonation the absence of lateral wall motion (Category 1) was observed more often in subjects with velar insufficiency and that lateral wall motion past the sides the velum (Categories 3 and 4) occurred less frequently.…”
Section: Lateral Pharyngeal Wall Closure In Patients With Velar Inadementioning
confidence: 99%
“…Over a several year period the author first categorized lateral wall movement among normal patients (Zwitman, 1974); then in patients with velar insufficiency (Zwitman, 1976). In the second study the findings revealed that during phonation the absence of lateral wall motion (Category 1) was observed more often in subjects with velar insufficiency and that lateral wall motion past the sides the velum (Categories 3 and 4) occurred less frequently.…”
Section: Lateral Pharyngeal Wall Closure In Patients With Velar Inadementioning
confidence: 99%
“…Radiology (Shprintzen et al, 1974) 2. Endoscopy (Pigott, Benson, and White, 1969;Taub, 1966;Willes and Stutz, 1972;Zwitman, Sonderman, and Ward, 1974) 3. Electromyography (Fritzell, 1969(Fritzell, , 1979 4.…”
Section: Instrumental Confirmation Of Vpi Diagnosismentioning
confidence: 99%
“…The velum moves in an upward and backward direction to articulate with the pharyngeal walls. Normal speakers exhibit differential patterns of muscle activity of the velum, lateral pharyngeal walls and posterior pharyngeal wall (Iglesias, Kuehn, & Morris, 1980; Shprintzen, Lencione, McCall & Skolnick, 1974; Zwitman, Sonderman, & Ward, 1974). That is, they achieve closure but the articulators contribute in different ways depending on the speaker.…”
Section: Introductionmentioning
confidence: 99%